2004
DOI: 10.5344/ajev.2004.55.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Response of Grapevine Defenses to UV—C Exposure

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This is illustrated by the reasonably good fits of the disease severity progression data to power functions having the same exponent of 3.19. With respect to the UV-C treatments investigated in this study, the observed delays in onset of downy mildew may be attributed to increased resistance to downy mildew induced by the treatments pr ior to infection (Bonomelli et al, 2004). Even if this could be substantiated in further experiments, however, the observed effect was relatively small.…”
Section: Year 2 Field Datamentioning
confidence: 66%
“…This is illustrated by the reasonably good fits of the disease severity progression data to power functions having the same exponent of 3.19. With respect to the UV-C treatments investigated in this study, the observed delays in onset of downy mildew may be attributed to increased resistance to downy mildew induced by the treatments pr ior to infection (Bonomelli et al, 2004). Even if this could be substantiated in further experiments, however, the observed effect was relatively small.…”
Section: Year 2 Field Datamentioning
confidence: 66%